Determinan kemampuan pemeriksa dalam mendeteksi fraud - Puspita Wulan Dari; Wahyudin Nor; Rasidah Rasidah (Jurnal Akuntansi Aktual, 2021)
AbstractFraudulent behavior continues to happen, showing that the eradication of this act is difficult. Fraud has costed a lot to the economy of the country. Hence, based on the UUD 1945, the government forms The Audit Board of The Republic Indonesia (BPK RI) which is an independent body that was responsible for auditing, management and financial responsibility of the state. This research aims to investigate the effect of examination experience, red flags, audit time budget pressure, workload, and personality type with the ability to detect fraud. This study used saturated sample method or census with the population of 32 independent BPK RI examiners in East Kalimantan Province. The data was collected through an online questionnaire and analyzed by using a multiple linear regression. The results of this study indicate that the audit experience and red flags variables affect the ability to detect fraud. Meanwhile, the audit time budget pressure, professional skepticism, workload, and personality type have no effect on the ability to detect fraud. This study can be used as a guide for examiners in carrying out their responsibilities, especially in detecting fraud.AbstrakTindakan kecurangan yang sampai saat ini masih sering terjadi menunjukkan sulitnya menghapuskan tindakan tersebut. Kecurangan telah banyak merugikan ekonomi negara. Penelitian ini bertujuan untuk menganalisis pengaruh pengalaman pemeriksaan, red flags, tekanan anggaran waktu pemeriksaan, beban kerja, dan tipe kepribadian terhadap kemampuan pemeriksa dalam mendeteksi kecurangan. Penelitian ini menggunakan sampel jenuh atau sensus dengan jumlah populasi 32 pemeriksa independen Badan Pemeriksa Keuangan (BPK) Provinsi Kalimantan Timur. Data dikumpulkan melalui kuesioner online, dan dianalisis dengan menggunakan regresi linear berganda. Hasil penelitian ini menunjukkan bahwa pengalaman pemeriksaan dan red flags berpengaruh terhadap kemampuan mendeteksi kecurangan. Namun, variabel tekanan anggaran waktu pemeriksaan, skeptisisme profesional, beban kerja, dan tipe kepribadian tidak berpengaruh terhadap kemampuan mendeteksi kecurangan. Penelitian ini bisa menjadi referensi bagi pemeriksa dalam menjalankan tugasnya, terutama dalam mendeteksi kecurangan.